H-infinity norm computation of multi-agent dynamical systems - Hòa, Nguyễn Đình; Phước, Nguyễn Doãn (Journal of Computer Science and Cybernetics, 2013)
In this paper, we propose a new method to computing the H_infinity norm of multi-agent dynamical systems(MADSs). Employing the generalized frequency variable (GFVs) framework, a class of MADSs can be represented by linear systems with GFVs. Then, an efficient method for H_infinity norm computation is proposed for MADSs whose communication topologies are diagonalizable. The calculation is derived in terms of an LMI problem which can be easily solved by off-the-shelf optimization solvers. Moreover, some numerical examples are introduced to demonstrate the efficiency of the proposed method.